Phagocytosis by the Retinal Pigment Epithelium: Recognition, Resolution, Recycling - Kwon, Whijin; Freeman, Spencer A. (Frontiers in Immunology, 2020)
Tissue-resident phagocytes are responsible for the routine binding, engulfment, and resolution of their meals. Such populations of cells express appropriate surface receptors that are tailored to recognize the phagocytic targets of their niche and initiate the actin polymerization that drives internalization. Tissue-resident phagocytes also harbour enzymes and transporters along the endocytic pathway that orchestrate the resolution of ingested macromolecules from the phagolysosome. Solutes fluxed from the endocytic pathway and into the cytosol can then be reutilized by the phagocyte or exported for their use by neighbouring cells. Such a fundamental metabolic coupling between resident phagocytes and the tissue in which they reside is well-emphasized in the case of retinal pigment epithelial (RPE) cells; specialized phagocytes that are responsible for the turnover of photoreceptor outer segments (POS). Photoreceptors are prone to photo-oxidative damage and their long-term health depends enormously on the disposal of aged portions of the outer segment. The phagocytosis of the POS by the RPE is the sole means of this turnover and clearance. RPE are themselves mitotically quiescent and therefore must resolve the ingested material to prevent their toxic accumulation in the lysosome that otherwise leads to retinal disorders. Here we describe the sequence of events underlying the healthy turnover of photoreceptors by the RPE with an emphasis on the signaling that ensures the phagocytosis of the distal POS and on the transport of solutes from the phagosome that supersedes its resolution. While other systems may utilize different receptors and transporters, the biophysical and metabolic manifestations of such events are expected to apply to all tissue-resident phagocytes that perform regular phagocytic programs.